Issues of the European Transport Policy and current state of EU funded transport research - Giannopoulos, G.A. (Yugoslav Journal of Operations Research; Vol 12 No 1 (2002): Vol. 12 No. 1, 2016)
This paper sets out the main lines of the existing EU Transport Policy, and transport research. After a brief description of the main elements of this policy, a discussion is given of its relation with transport research and the basic orientations that existed under the previous Framework Programmes for EU funded research. Then the main elements of the policy for the new (6th) Framework Program are presented.